THE BANKRUPTCY OF FOREIGN CAPITAL COMPANIES AND INDONESIAN LABOR PROTECTION - Farahni, Fadilah Nariza (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
Indonesia as a destination for investment will open an opportunity to foreign investor to come and invest their money in Indonesia. As the time goes by, those foreign companies cannot survive due to tight competition that may lead to bankruptcy. In Indonesia, Law No. 37 Year 2004 about bankruptcy and debt moratorium/suspension of payment has not been arranged it in detail about foreign stock company bankruptcy. Therefore, this research aims to examine 2 aspects, which are first, to show that foreign stock company in Indonesia can be bankrupted. Second, to explain the rights of Indonesian employees that works in that bankrupted company. From this research, we found that foreign stock company in Republic of Indonesia area can be bankrupted based on Act No. 25 Tahun 2007 about capital investment, which says that foreign capital investment must be in a form of Limited Liability Company based on the Indonesian law. This clearly states that foreign stock company in Indonesia should obey the law and order of Republic of Indonesia. Indonesian labor's rights for the labour who works for foreign stock company that experiences bankruptcy based on Labour Law No. 13 Year 2003 Act 165 states that the labor's rights include: severance payments, long service payment and com-pensation payment.